Feasibility of 3D printed Co-Cr alloy for dental prostheses applications - Camacho Presotto, Anna Gabriella; Cordeiro, Jairo Matozinho; Camacho Presotto, Joao Gabriel [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Cruz, Nilson Cristino da [UNESP]; Landers, Richard; Barao, Valentim Adelino R.; Mesquita, Marcelo Ferraz (Elsevier B.V., 2021)
The aim of this study was to characterize the surface, microstructural, mechanical, and electrochemical properties of Selective Laser Melting (SLM) 3D-printed Co-Cr alloy when compared with casting and Soft Metal Block (SMB) milling techniques for dental prostheses applications. Specimens with specific dimensions were fabricated by cast, SMB, and SLM technologies with their respective commercially available Co-Cr alloys. Several techniques were carried out to characterize the specimens in terms of surface morphology, chemical composition, microstructure, surface free energy, and mechanical properties. Metal-ceramic bond strength was evaluated with the 3-point bend test. Standard electrochemical tests were conducted in artificial saliva (pH of 6.5). Data were evaluated at a significance level of 5%. Similar microstructure patterns (gamma-phases and epsilon-phases), surface morphology, roughness, and surface free energy were observed among groups (p > 0.05, ANOVA). The elemental composition provided by energy-dispersive spectroscopy confirmed the manufacturer's information on the alloys used. SLM technology provided a fine-grained homogeneous and less porous microstructure. Xray photoelectron spectroscopy analysis suggested a thicker oxide film on SLM surfaces. Highest values of Vickers microhardness, flexural strength, elastic modulus, and metal-ceramic bond strength were found for the SLM group (p < 0.05, Tukey's HSD test). The SLM group displayed greater electrochemical stability, presenting higher polarization resistance (Rp(tot)), corrosion potential (E-corr), and pitting potential (E-pit) values (p < 0.05, Tukey's HSD test). SLM technology revealed feasible surface, microstructural, mechanical, and electrochemical properties and can be a promising option for the fabrication of dental prostheses. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Selective laser melting; Cobalt-chromium alloys; Dental application; Physicochemical properties